Cu-mediated synthesis of differentially substituted diazepines as AChE inhibitors; validation through molecular docking and Lipinski's filter to develop novel anti-neurodegenerative drugs. Issue 11 (1st June 2019) - Sudhapriya, N.; Manikandan, A.; Kumar, M. Rajesh; Perumal, P.T.
Graphical abstract: Abstract: A highly efficient Cu-mediated route for the synthesis of fused [1, 2, 3]triazolo[1, 4]diazepines has been developed by azidation-cyclization of 2-bromo- N -propargylamines in a one-pot fashion. The key highlight of the present work is that the 2-bromo- N -propargylamines are prepared through the A 3 -reaction of cyclic amines such as isoquinoline and decarboxylative coupling of proline and pipecolinic acid with 2-bromo benzaldehyde and alkyne. As preliminary, these compounds were analyzed for their most probable bioactivity using various in silico tools. The recognized anti-neurodegenerative activity potential was assessed by molecular docking, AChE inhibition activity in erythrocytes and DPPH radical scavenging activity potentials possessed by the compounds. With a relative AChE inhibition activity of 97% (IC50 0.25 ± 0.02 µM), compound5d identified as the most active compound. Druggability of these compounds also evaluated through Lipinski's filter and other ADMET tools for the betterment of selective execution of in vitro and in vivo activities of the screened compounds cautiously.